Effects of the compound extracts of Caprifoliaceae and Scutellaria baicalensis Georgi on the intestinal microbiota and antioxidant function - Zhang, Shunfen; Lv, Huiyuan; Cai, Xueying; Tang, Shanlong; Zhong, Ruqing; Chen, Liang; Zhang, Hongfu (Frontiers in Microbiology, 2024)
According to the Chinese encyclopedia “Ben Cao Gang Mu” (AD 1552–1578), Caprifoliaceae and Scutellaria baicalensis Georgi are used in traditional Chinese medicine to clear heat, detoxify, and treat wind-heat colds, upper respiratory tract infections, and pneumonia. However, the mechanism and the effects of the compound extracts of Caprifoliaceae and Scutellaria baicalensis Georgi on intestinal health remain unclear. From the perspective of intestinal microbes, this study assessed the antioxidant, anti-inflammatory, and intestinal protective properties of Caprifoliaceae and Scutellaria baicalensis Georgi. Mice received diets with or without Caprifoliaceae and Scutellaria baicalensis Georgi extractive (BCA) for 2 weeks in this study. The results showed that BCA increased body weight gain, feed intake, and catalase (CAT) content in the mice but reduced γ-glutamyl transpeptidase (γ-GT) content in the serum (p < 0.05). BCA improved the Sobs, Chao, and Ace indices, as well as the number of Campylobacterota, Patercibacteria, and Desulfobacterota in the colon microbiota, while it decreased the Firmicutes phylum (p < 0.05). At the genus level, BCA increased Candidatus_Saccharimonas, Helicobacter, unclassified_f_Lachnospiraceae, Alistipes, norank_f_norank_o_Clostridia_vadinBB60_group, norank_f_Ruminococcaceae, unclassified_f_Ruminococcaceae, etc. abundance (p < 0.05), but it significantly decreased Lactobacillus and Lachnospiraceae_UCG_001 abundance (p < 0.05). Moreover, BCA improved the concentration of acetic acid, butyric acid, propionic acid, valeric acid, and isovaleric acid and diminished the concentration of isobutyric acid (p < 0.05). Correlation analysis shows that the changes in short-chain fatty acids and antioxidant and inflammatory indices in the serum were significantly correlated with the BCA-enriched microbiota. This study supplemented a database for the application of Caprifoliaceae and Scutellaria baicalensis Georgi in clinical and animal production.